Efficacy of Chemical Insecticides against Citrus Leaf Miner (CLM) (Phyllocnistis citrella Stainton) in South-western Bangladesh (SAARC Journal of Agriculture, 2025)
The citrus leaf miner (CLM) is a major threat to citrus production in the World including Bangladesh. Insecticides are a commonly utilized and effective method to manage this pest in field conditions. However, judicious application of insecticides is crucial for successful and cost-effective management of CLM. Therefore, the present study aimed to evaluate the efficacy of insecticides namely imidacloprid, cypermethrin, chlorpyrifos and abamectin, respectively, against CLM in field conditions, maintaining a randomized complete block design with three replicates. All the treatments applied in experiment had preventive action against the CLM compared with the untreated control. Results revealed that among the treatments, the imidacloprid statistically provided the lowest leaf infestation after 1st Spray (6.66% and 4.27%), 2nd Spray (5.76% and 2.50%), 3rd Spray (0.84% and 0.11%) relative to control. Among insecticides applied, imidacloprid treated plots demonstrated the most significant reduction in larval counts all through the sprays. However, for natural enemies (ladybird beetle, Coccinella septempunctata) count, statistically maximum number of NEs was observed in untreated control plots relative to treated plots. Based on the findings, it could be inferred that imidacloprid was proved most effective in controlling CLM compared to other applied insecticides.SAARC J. Agric., 23(1): 254-263 (2025)